Relationship Between Household Economic Status and Childhood Micronutrient Deficiency in India: An Evidence from a National Level Representative Survey - Ghosh, Atanu; Bisai, Samiran (International Journal of Nutrition, 2026)
The high prevalence of anemia among children and adolescents in India is still an overwhelming problem. Not only that, there is also a considerable deficiency of various micronutrients such as Vitamin A, Vitamin B12, Vitamin D, serum ferritin, Zinc and Folate etc. in children. These micronutrients have several functional roles for the normal growth and development of children. Unfortunately, recent studies on public health and nutrition intervention have so far focused less on these micronutrition and more on anemia and nutrition. Data for this study obtained from the Comprehensive National Nutrition Survey (CNNS 2016-18), a nationally representative survey covering different age group. Specifically, it includes information on 9767 children aged 1-4 years. Out of these surveyed children biomarker data for hemoglobin, serum ferritin, zinc, folate, vitamin A, vitamin B12 and Vitamin D were collected from 8242 children. Micronutrient deficiencies were identified based on WHO and other established cut-off criteria. Wealth quintiles were computed to identify household economic inequality. The prevalence of anemia at the national level was 40.7%. Among micronutrients, folate (22.9%) and zinc (18.7%) deficiencies were most commonly observed, followed by vitamins A (18.3), vitamin B12 (13.8%) and vitamin D (14.0%). Iron deficiency as measured by ferritin was present in 31.6% of children. It is alarming that nearly one in three children (32.8%) suffer from deficiencies in two or more micronutrients. Clear socioeconomic disparities were observed for all micronutrient deficiencies (MND); children in the poorest groups had significantly higher levels of micronutrient deficiencies than children in the richest groups. Among the states, Gujarat and Madhya Pradesh had the highest overall micronutrient deficiencies, while West Bengal and Kerala had the lowest. This clearly shows that a large proportion of preschool children in India suffer from anemia and MND, with the prevalence being even more alarming in lower socio-economic settings. This study suggests that there is a need to move beyond single-nutrient interventions and implement comprehensive, multi-micronutrient supplementation or food fortification strategies seamlessly into the existing national health and nutrition programs.
Keywords: Micronutrient deficiency; preschool children; low-income households; socioeconomic status; CNNS; India